Coccidioidomycosis among persons undergoing lung transplantation in the coccidioidal endemic region. Issue 4 (22nd June 2017) - Chaudhary, Sachin; Meinke, Laura; Ateeli, Huthayfa; Knox, Kenneth S.; Raz, Yuval; Ampel, Neil M.
Abstract: Background: Coccidioidomycosis, an endemic fungal infection, is more likely to be symptomatic and severe among those receiving allogeneic transplants. While several case series have been published for various transplanted organs, none has described the incidence and outcomes in those receiving lung transplants within the coccidioidal endemic region. Methods: Patients receiving a heart‐lung, single‐lung, or bilateral‐lung transplantation at the University of Arizona between 1985 and 2009 were retrospectively reviewed. Results: Coccidioidomycosis occurred post transplantation in 11 (5.8%) of 189 patients. All but one patient was diagnosed with pulmonary coccidioidomycosis and only one had a history of prior coccidioidomycosis. Two patients received transplants from donors found to have coccidioidomycosis at the time of transplantation and one death was directly attributed to coccidioidomycosis. The risk of developing active coccidioidomycosis was significantly higher if the patient did not receive some type of antifungal therapy post transplantation ( P <.001). Conclusion: Within the coccidioidal endemic region, post‐transplantation coccidioidomycosis was a definable risk among lung transplant recipients. Use of antifungals appeared to reduce this incidence of disease. Almost all cases resulted in pulmonary disease, suggesting that the lung is the primary site of infection.